THE DHAMMADHIPATEYYA : THE IDEAL OF CREATING BALANCE FOR STATE SOVEREIGNTY - รักษาเมือง, สุริยา (Journal of MCU Social Science Review, 2018)
The objectives of this search were 1) to study the concept of Dhammadhipateyya, 2) to study the factor of Dhammadhipateyya and 3) to propose The Dhammadhipateyya : The Ideal of Creating Balance for State Sovereignty. The methodology of this research was documentary research. The findings were as follows; 1) Dhammadhipateyya was the supremacy of the law of truth and righteousness. It’s principles that use to support the governance. 2) The factors of Dhammadhipateyya were; 1) Dhammathiti, 2) Dhammaniti and 3) Dhammamati. 3) The ideal Dhammadhipateyya were; 3.1) State governors must hold firmly in the righteousness to create the balance for state sovereignty, 3.2) State governors must establish a righteousness system and laws and 3.3) State governors must have a rightful resolution.